America In the Early of the 1920s And Gatsby as A Symbol of American Dream - Mariwan Hwayyiz Rustum (QALAAI ZANIST JOURNAL, 2022)
This paper is going to follow-up the cultural studies that concentrate on cultural authority and presents the concept of the power of the main groups to dominate society. It'll also raise the question of how people lived within the 1920s in America. The goal is to analyze how to use cultural studies, Scott Fitzgerald Gatsby's great book so on reach some conclusions about the depiction of classes and aristocratic forces to manage vulnerable groups. Specifically, this research focuses on Jay Gatsby's struggle to counter dominance of aristocratic groups, within which the rich excel. Within the story, the rich new group, represented by Jay Gatsby, lives in West Egg, whiles the aristocratic group, represented by Tom Buchanan, lives in East Egg. Analysis and discussion of the novel reveal that cash incorporates a great influence on the characters. Those that relied on it to satisfy a particular dream; Gatsby wants to reclaim Daisy with the ability of legal or illegal money.